1997
DOI: 10.1002/hep.510250342
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment virus load and multiple amino acid substitutions in the interferon sensitivity-determining region predict the outcome of interferon treatment in patients with chronic genotype 1b hepatitis C virus infection

Abstract: biochemical and histological improvement. 3,4 Several factors Hepatitis C virus (HCV) genotype 1b and high precan predict a poor response to interferon therapy, e.g., high treatment virus load are predictive factors of poor repretreatment virus load, genotype 1b, advanced histological sponse to interferon therapy in patients with chronic changes, lower serum ferritin level, and a high degree of hepatitis C. To further examine the factors predicting amino acid substitutions of the hypervariable region (for reth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

18
136
6

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(160 citation statements)
references
References 18 publications
18
136
6
Order By: Relevance
“…This sequence has been termed the interferon sensitivity-determining region (ISDR). These results were then confirmed by other Japanese studies [11][12][13][14][15] , but were never in accordance with most Western European [16][17][18][19][20] and American studies [21][22][23] , in which most of the ISDR sequences harbored an intermediate profile.…”
Section: Introductionsupporting
confidence: 64%
“…This sequence has been termed the interferon sensitivity-determining region (ISDR). These results were then confirmed by other Japanese studies [11][12][13][14][15] , but were never in accordance with most Western European [16][17][18][19][20] and American studies [21][22][23] , in which most of the ISDR sequences harbored an intermediate profile.…”
Section: Introductionsupporting
confidence: 64%
“…39 ISDR mutations are also shown to be related to the serum HCV-RNA levels. 13,16 Therefore, in HCV-2 infection, the amino acid changes in the homologous region might also be associated with the effect of interferon therapy. The present analysis of the C-terminal half of NS5A of HCV-2 confirmed that there is a significant association among the effect of interferon therapy, serum HCV-RNA levels, and the amino acid changes in NS5A2163-2228 of HCV-2a (the corresponding region of ISDR of HCV-1b, NS5A2193-2228 plus its upstream region) or NS5A2193-2228 alone.…”
Section: Discussionmentioning
confidence: 99%
“…The present findings of HCV-2a infection on the interrelationship among interferon efficacy, viral load, and NS5A mutations are consistent with the observation seen in HCV1b. 13,16,39 The mechanism of this interrelation is still unclear, but an association between the amino acid changes in NS5A and reduced serum HCV-RNA level suggest an important role of the NS5A protein in the proliferation of HCV. Otherwise, the NS5A protein would confer the resistance to antiviral effects of interferon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations